HIV-1 Variable Loop 2 and its Importance in HIV-1 Infection and Vaccine Development - Rao, Mangala; K. Peachman, Kristina; Kim, Jiae; Gao, Guofen; R. Alving, Carl; L. Michael, Nelson; B. Rao, Venigalla (Current HIV Research, 2013)
A vaccine that can prevent the transmission of HIV-1 at the site of exposure to the host is one of the best hopes to control the HIV-1 pandemic. The trimeric envelope spike consisting of heterodimers, gp120 and gp41, is essential for virus entry and thus has been a key target for HIV-1 vaccine development. However, it has been extremely difficult to identify the types of antibodies required to block the transmission of various HIV-1 strains and the immunogens that can elicit such antibodies due to the high genetic diversity of the HIV-1 envelope. The modest efficacy of the gp120 HIV-1 vaccine used in the RV144 Thai trial, including the studies on the immune correlates of protection, and the discovery of vaccine-induced immune responses to certain signature regions of the envelope have shown that the gp120 variable loop 2 (V2) is an important region. Since there is evidence that the V2 region interacts with the integrin α4β7 receptor of the host cell, and that this interaction might be important for virus capture, induction of antibodies against V2 loop could be postulated as one of the mechanisms to prevent the acquisition of HIV-1. Immunogens that can induce these antibodies should therefore be taken into consideration when designing HIV-1 vaccine formulations.
Keywords: gp120